(untitled) (Ustozlar uchun, 2025)
Annotation: This article explores the historical development and evolution of the English language from its earliest origins to its modern global status. It examines four main periods: Old English, Middle English, Early Modern English, and Modern English. Each stage is analyzed in terms of linguistic changes, external influences such as invasions, cultural and intellectual movements, and technological innovations. The study highlights how English evolved from a set of Germanic dialects into a global lingua franca spoken by billions worldwide. Understanding the history of English helps us appreciate its richness, flexibility, and ongoing transformation.